Appendiceal adenocarcinoma presenting as left-sided large bowel obstruction, a case report and literature review - Aljarabah, Moayad M (BioMed Central, 2007)
BACKGROUND: appendiceal tumours are rare, they may be encountered unexpectedly in any acute or elective abdominal operation, many of these tumours are not appreciated intraoperatively and are diagnosed only during formal histopathological analysis of an appendicectomy specimen. Herein we present a case of appendiceal adenocarcinoma presenting as left-sided large bowel obstruction, we also review the literature of unusual presentations of appendiceal tumours. CASE PRESENTATION: we report a case of left sided large bowel obstruction found to be secondary to an appendiceal adenocarcinoma. The patient presented with abdominal pain, distension and constipation, CT scan showed large bowel obstruction thought to be due to a sigmoid tumour, on laparotomy the appendix was also noted to be abnormal. A low Hartman's was performed with en-bloc total hysterectomy and bilateral salpigo-oophorectomy. A separate ileocaecal resection with end ileostomy was also performed, pathology specimens showed that the primary neoplasm was the appendix with metastasis to the distal sigmoid. CONCLUSION: appendiceal tumours are rare, they usually present as acute appendicitis, other presentations are far less common.